Platelet-rich Fibrin: A Systematic Review of Its Action - Puspa Zuleika; Irsan Saleh; Krisna Murti; Iche Andriyani Liberty; Legiran; Irfanuddin; Agus Surono (Wolters Kluwer Medknow Publications, 2024)
Purpose We aim to conduct a literature review on actions of platelet-rich fibrin (PRF), preclinical studies in PRF utility, and its potential uses in clinical settings. Methods We conducted a literature review based on primary studies conducted on PubMed and Europe PMC between 2012 and 2022. We included 42 articles in this review from the results of our search. Results Epithelial tissues act as a barrier from mechanical, chemical, and temperature damage. Naturally, hemostasis acts to reduce blood loss and creates initial fibrin matrices after traumatic events or injuries. PRF is a second-generation platelet concentrate, commonly made in the form of leukocyte and PRF due to leukocyte content. Fibrin matrices in PRF allow more sustained growth factors release when compared to PRP, the first-generation platelet concentrate. PRF comes from increased proliferation and differentiation mediated by reduced proliferation of inflammatory cells and sustained release of growth factors and cytokines. Conclusions PRF action comes from increased proliferation and differentiation from growth factors and cytokines. PRF may reduce inflammation and fibrosis to improve soft-tissue and bone healing and allow for better graft integration.